2017
DOI: 10.3126/jkmc.v5i2.18411
|View full text |Cite
|
Sign up to set email alerts
|

Level of physical activity and obesity among the adolescent school children in Bhaktapur: A cross-sectional pilot study

Abstract: Background: Physical activity is crucial for overall health and well-being of an individual. As childhood obesity has emerged as a serious public health concern, physical activity is a proven tool for prevention and treatment of this type of obesity. As lifestyle and behavior pattern is formed at the adolescence age, it is essential that healthy lifestyle and good food habit should start at this age. Hence, we aimed to fi nd the level of physical activity and obesity among the adolescent school children in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…9 A cross-sectional pilot study conducted at a randomly selected private school in Bhaktapur showed that out of 83 students, 12% were either overweight or obese which is slightly higher than the prevalence found in the present study. 10 Another cross-sectional study in Kaski district among adolescents showed the prevalence of overweight and obesity of 8.1% out of which 5.8% were overweight and 2.3% were obese. 11 Similarly, the results of a study conducted in Iranian children and adolescents revealed that 9.7% were overweight and 11.9% were obese.…”
Section: Discussionmentioning
confidence: 97%
“…9 A cross-sectional pilot study conducted at a randomly selected private school in Bhaktapur showed that out of 83 students, 12% were either overweight or obese which is slightly higher than the prevalence found in the present study. 10 Another cross-sectional study in Kaski district among adolescents showed the prevalence of overweight and obesity of 8.1% out of which 5.8% were overweight and 2.3% were obese. 11 Similarly, the results of a study conducted in Iranian children and adolescents revealed that 9.7% were overweight and 11.9% were obese.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, leisure time through physical activity among adolescents has been recognized as a healthy lifestyle habit and promoted in developed countries [59]. Besides, recent studies by Misra and Grason [60] and Sainju and Manandhar [61] presented further evidence that physical activity increased during childhood and decreased during adolescence; however, this decline was more conspicuous in girls than in boys. Based on our results, the same held true for Iranian adolescent boys, where there was a significantly low level of physical activity among overweight and obese boys.…”
Section: Discussionmentioning
confidence: 99%